(untitled) (Qo‘qon DPI. Ilmiy xabarlar jurnali, 2026)
In today’s educational space, artificial intelligence (AI) is becoming increasingly important, opening up new horizons for individualized and effective learning. The methodology for using AI in learning involves the integration of intelligent systems and algorithms into the educational process in order to optimize educational material, personalize learning, and automate routine tasks. One of the key areas is adaptive learning. AI-based systems analyze each student’s academic performance, strengths, and weaknesses, offering individually tailored assignments and learning pacing. This allows the student not to waste time on the material already mastered and concentrate on problem areas, which significantly increases the effectiveness of learning.